Lissencephaly and cerebellar hypoplasia in a goat - José Rômulo Soares dos Santos (Ciência Rural, 2013)
A case of lissencephaly and cerebellar hypoplasia was observed in a 30-day-old goat. The goat presented with sternal recumbence, absence of a menace response, intention tremors, ataxia, and nystagmus. The goat was euthanized and necropsied after having been hospitalised for eleven days. At necropsy, the surface of the brain was found to be smooth, the cerebral sulci and gyri were absent, and the cerebellum was reduced in size. Histologically, the grey matter and white matter were thicker and thinner than normal in cortices, respectively. The neurons were randomly arranged in the grey matter. In the cerebellum, the layers were disorganised, and cells were heterotopics. The histologic and gross lesions observed in this animal are characteristic of lissencephaly associated with cerebellar hypoplasia. The presence of a single goat affected suggests that the malformation was not of infectious origin and because lissencephaly is a malformation not previously described in goats, it is unlikely this case was inherited.